RESPON PASAR TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN TERINDEKS SRI-KEHATI - Humaira, Alika; Hasnawati, Sri (Faculty of Economics and Business University of Lampung, 2024)
The sustainability report represents the development of the sustainability concept and commitment to achieving the United Nations’ SDGs performed by companies. One of the institutions that contribute to enhancing the implementation of the sustainability concept in Indonesia is the Yayasan Kehati, with one of its stock indices named SRI-KEHATI, which is well-known among Indonesian investors. This research examines the effect of the disclosure of economic, environmental, and social indicators in the sustainability report on the company’s market performance. The population of this study is companies listed on the Indonesia Stock Exchange and included in the SRI-KEHATI index from 2018 to 2022, with a sample collection of 12 companies using purposive sampling techniques. Using multiple linear regression for panel data and the Eviews data processing software, this research finds that economic and environmental indicators in the sustainability report positively affect market performance, while social indicators in the sustainability report negatively impact market performance. This research indicates that the sustainability report influences investors’ decision-making and successfully impacts the company’s market performance. Keywords: Sustainability; Disclosure; Performance; Investor response Abstrak Sustainability report merupakan wujud dari perkembangan konsep sustainability dan komitmen mencapai SDGs PBB yang dilakukan oleh perusahaan. Salah satu instansi yang ikut andil meningkatkan implementasi konsep sustainability di Indonesia adalah Yayasan Kehati dengan salah satu indeks sahamnya yang bernama SRI-KEHATI dan sudah cukup dikenal oleh investor Indonesia. Penelitian ini menguji pengaruh pengungkapan indikator ekonomi, lingkungan, dan sosial sustainability report terhadap performa pasar perusahaan. Populasi penelitian ini adalah perusahaan yang terdaftar di Bursa Efek Indonesia dan termasuk dalam indeks SRI-KEHATI pada tahun 2018 hingga 2022 dan pengambilan sampel sebanyak 12 perusahaan dengan menggunakan teknik purposive sampling. Dengan menggunakan regresi linier berganda untuk data panel dan menggunakan software pengolah data berupa Eviews, penelitian ini menemukan bahwa indikator ekonomi dan lingkungan dalam sustainability report mempengaruhi performa pasar secara positif, sedangkan indikator sosial dalam sustainability report berpengaruh negatif pada performa pasar. Penelitian ini menunjukkan bahwa pengambilan keputusan investor terpengaruh oleh sustainability report dan berhasil memberikan pengaruh bagi performa pasar perusahaan. Kata Kunci: Sustainability, Pengungkapan, Performa, Respon Investor